Renaissance Papers 2018 - Pearce, Jim (Director of Graduate Studies); Risvold, Ward J.; Sanders, Suzanne J. (Camden House, 2019)
Sixty-fifth annual volume, focusing notably on Shakespearean drama and the poetry of early modern England but with essays on a variety of other topics relevant to the period.